Government Challenges in Simplifying Tobacco Excise Rate Structure to Minimize Excise Avoidance of Cigarette Manufacturer in Indonesia - Maria R.U.D. Tambunan; M. Nova Nurvrianto (Magister Ilmu Administrasi Publik, 2020)
The aim of this research is to analyses the government challenge to simplify tobacco excise rate structure to minimize excise avoidance potentially performed by Cigarette Manufacture in Indonesia. Indonesia government manages to simplify the structure of tobacco excise rate from previously 12 layers into 5 layers as planned in 4 years roadmap (2018 - 2021). The aim of this initiative is to minimize excise avoidance practices, that is expected to optimize tobacco excise revenues. This policy involves various actors and gets the pros and cons of stakeholders. Basically, simplifying tobacco rate structure objective should be to discourage cigarettes consumption. This research is descriptive qualitative research, data was collected through desk study and field study through in-depth interview with key informants. The results showed that consumption control before and after the initiatives (regulated by 146 /PMK.10 /2017) did not show a positive trend. Meanwhile, there was an intervention from the tobacco industry on the process of policy formulation and the difficulty of getting agreement in the policy formulation process from related stakeholders. Finally, the initiative to further simplifying the layers has been decided to postpone in 2019.This research clearly shows that competition among stakeholders exists. The government even on the difficulty and dilemma situation to make policy decision on what priority it should undertake firstly.